Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M181 - Peter Brandt; Anne-Cathrin Wölfl (PANGAEA, 2023)
Multibeam bathymetry raw data was recorded in the South Atlantic during cruise M181 that took place between 2022-04-17 and 2022-05-28. The data was collected using the ship extquotesingles own Kongsberg EM 122. One sound velocity profile (SVP) was applied on the data for calibration. Please see environmental data (zip file) and the cruise report for details.